RESPON PENGGUNA TERHADAP APLIKASI KANJI HUNTER - Lutfhi Fauzi; Pitri Haryanti; Soni Mulyawan Setiana (Program Studi Sastra Jepang, Universitas Komputer Indonesia Bandung, 2017)
Language has important function, beside using it as communication media, but also can be used as media to aspire idea, mind and aspiration. Thereâ€™s also dificulity when learning foreign language, especially learning Japanese language. Tenses, kanji words etc can be obstacle to learning Japanese language. Emprical experience prove that foreign students has problem learning kanji when studying Japanese language. Based of this problem, writer create â€œKanji Hunterâ€ education game as kanji media learning to make learning kanji easier. This study aimed to obtain an overview of feedback fromÂ respondents about â€œKanji Hunterâ€. This research design was descriptive qualitative research. The data were taken through questionarre to the 30 students of Japanese Department of Unikom. Â The result is about 1389 criterium value, that means itâ€™s in good interval. With this â€œKanji Hunterâ€ application based Adobe Flash as basic kanji media learning is expected to make enthusiastic foreign student to learn kanji words dan make it easier.